2011
DOI: 10.4061/2011/695413
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular APP Domain Regulates Serine‐Palmitoyl‐CoA Transferase Expression and Is Affected in Alzheimer′s Disease

Abstract: Lipids play an important role as risk or protective factors in Alzheimer's disease (AD), a disease biochemically characterized by the accumulation of amyloid beta peptides (Aβ), released by proteolytic processing of the amyloid precursor protein (APP). Changes in sphingolipid metabolism have been associated to the development of AD. The key enzyme in sphingolipid de novo synthesis is serine-palmitoyl-CoA transferase (SPT). In the present study we identified a new physiological function of APP in sphingolipid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 76 publications
1
60
0
Order By: Relevance
“…To determine the effect of AICD (sequence in 1-letter code: KMQQNGYENPTYKFFEQMQN) (2µM) (Genscript Corporation, Piscatway, USA) synthetic peptides were incubated for 9 days in cell culture. Utilizing this method it has been previously shown that AICD is efficiently taken up and biologically active [30,31]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the effect of AICD (sequence in 1-letter code: KMQQNGYENPTYKFFEQMQN) (2µM) (Genscript Corporation, Piscatway, USA) synthetic peptides were incubated for 9 days in cell culture. Utilizing this method it has been previously shown that AICD is efficiently taken up and biologically active [30,31]. …”
Section: Methodsmentioning
confidence: 99%
“…After isolation of the lipid phase as described above, 3ml szintilation solution (Perkin Elmer, Rodgau-Jügesheim, Germany) was added, mixed and radioactivity was measured by a Tri-Carb 2800TR (Perkin Elmer, Rodgau-Jügesheim, Germany) [31,41,42,43]. The assay was validated using a specific GCS inhibitor, DL-PDMP (5µM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these alterations, abnormal sphingolipid metabolism has been reported in AD tissues (van Echten‐Deckert & Walter, 2012). Specifically, there is an upregulation of de novo ceramide synthesis (Grimm et al , 2011) and an increase in the activity of sphingomyelinase (SMase), which catabolizes sphingomyelin (SM) into ceramide (Filippov et al , 2012). These alterations act synergistically to increase ceramide content in AD brains (Filippov et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The α-secretase cleaves APP within the Aβ domain, thus precluding the formation of Aβ peptides. The γ-secretase cleavage of βCTF/C99 and αCTF/C83 liberates the APP intracellular domain (AICD), which translocates to the nucleus and regulates gene expression [306][307][308][309][310].…”
Section: Proteolytic Processing Of App Amyloidogenic App Processingmentioning
confidence: 99%